What Do True Gender Ratios and Stereotype Norms Really Tell Us? - Gygax, Pascal M.; Garnham, Alan; Doehren, Sam (Frontiers in Psychology, 2016)
We present a Focused Review on work that was conducted to compare perceived distributions of men and women in occupations and other social roles with actual real world distributions. In previous work, we showed that means for the two sources were similar and the correlation between them was high. However, in the present paper, although we argue that comparing subjective gender stereotype norms and real world data about gender ratios is an interesting endeavour, we also discuss the limits to and difficulties in trying to determine the causal relationship between them. Most crucially, we argue that our data does not allow us to deduce with certainty that subjective gender norms are based directly on gender ratios.